Behaviours and Beliefs Related to Whistleblowing Against Doping in Sport: A Cross-National Study - Bondarev, Dmitriy; Barkoukis, Vassilis; Lazuras, Lambros; Bochaver, Konstantin; Oudra, Despoina; Theodorou, Nikolaos (Frontiers in Psychology, 2022)
Background Whistleblowing has been recognized as an important deterrent of doping in elite competitive sport. The present study examined athletes’ knowledge of external whistleblowing channels and on how and where to report doping misconduct, perceived trust in different whistleblowing reporting channels, whistleblowing behaviour and athletes’ reasons for reporting (or not) doping misconduct. Methods Athletes from Greece (n = 480), the Russian Federation (n = 512) and the United Kingdom (n = 171) completed a structured questionnaire on demographics, knowledge of different whistleblowing channels, perceived trust in internal and external whistleblowing channels, past whistleblowing behaviour and reasons for reporting (or not) doping misconduct. Results The British athletes reported greater awareness of whistleblowing reporting channels (e.g., WADA’s Speak Up and IOC’s reporting platform) than did athletes from Greece (all p < 0.001) and Russia (p = 0.07, and p = 0.012) respectively. However, British athletes reported the lowest scores on knowledge of how and where to report doping misconduct, as compared to athletes from Greece and Russia. The majority of respondents reported greater trust to their coach or a club manager than to other whistleblowing channels, however, responses regarding other channels varied by country. Among athletes who detected doping misconduct 62% of athletes did not report it, while 38% reported it. Reasons for and against reporting doping misconduct reflected in eight themes that were identified using thematic analysis. Conclusion Athletes showed low awareness of external whistleblowing channels and they predominantly trusted internal whistleblowing channels. Sportspersonship, confidence in resources and personal benefits were among the reasons that facilitate reporting doping misconduct. The present findings indicate that cultural context may play a role in the ways athletes perceive whistleblowing, and this should be taken into account by future interventions to promote the reporting of doping misconduct.